OHMS**: Phytoplasmas dictate changes in sieve-element ultrastructure to accommodate their requirements for nutrition, multiplication and translocation. (1st February 2016) - Musetti, Rita; Pagliari, Laura; Buxa, Stefanie V.; Degola, Francesca; De Marco, Federica; Loschi, Alberto; Kogel, Karl-Heinz; van Bel, Aart J. E.
ABSTRACT: Phytoplasmas are among the most recently discovered plant pathogenic microorganisms so, many traits of the interactions with host plants and insect vectors are still unclear and need to be investigated. At now, it is impossible to determine the precise sequences leading to the onset of the relationship with the plant host cell. It is still unclear how phytoplasmas, located in the phloem sieve elements, exploit host cell to draw nutrition for their metabolism, growth and multiplication. In this work, basing on microscopical observations, we give insight about the structural interactions established by phytoplasmas and the sieve element plasma membrane, cytoskeleton, sieve endoplasmic reticulum, speculating about a possible functional role.